2017
DOI: 10.1186/s13045-017-0432-0
|View full text |Cite
|
Sign up to set email alerts
|

T-ALL and thymocytes: a message of noncoding RNAs

Abstract: In the last decade, the role for noncoding RNAs in disease was clearly established, starting with microRNAs and later expanded towards long noncoding RNAs. This was also the case for T cell acute lymphoblastic leukemia, which is a malignant blood disorder arising from oncogenic events during normal T cell development in the thymus. By studying the transcriptomic profile of protein-coding genes, several oncogenic events leading to T cell acute lymphoblastic leukemia (T-ALL) could be identified. In recent years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 163 publications
0
14
0
Order By: Relevance
“…Medical advances have improved the survival of adult patients with acute lymphoblastic leukemia (ALL) over the past few decades. T cell acute lymphoblastic leukemia (T-ALL) is one of the most aggressive hematologic malignancies, accounting for up to 10–15% of pediatric ALL and 25% of adult ALL cases [ 1 ], and arises from the malignant transformation of T cell progenitors [ 2 , 3 ]. Although high-dose multi-agent chemotherapy is clinically effective in most cases, primary drug resistance and relapse are frequently observed [ 4 ], preventing T-ALL from being cured [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Medical advances have improved the survival of adult patients with acute lymphoblastic leukemia (ALL) over the past few decades. T cell acute lymphoblastic leukemia (T-ALL) is one of the most aggressive hematologic malignancies, accounting for up to 10–15% of pediatric ALL and 25% of adult ALL cases [ 1 ], and arises from the malignant transformation of T cell progenitors [ 2 , 3 ]. Although high-dose multi-agent chemotherapy is clinically effective in most cases, primary drug resistance and relapse are frequently observed [ 4 ], preventing T-ALL from being cured [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…21 The profiles of these miRNAs could differ based on the tumor type and, hence, might provide novel biomarkers for diagnosis of many cancers. 22,23 It has been shown the expression levels of miR-181a, miR-128-3P and miR-142-3p were significantly up-regulated in T-ALL patients, 1,4,24 whereas miR-204, miR-101 and miR-193b-3p were down-regulated. 2,24,25 Some studies have indicated that FBXW7 dysregulates important signaling pathways including Notch1 and Notes: a Targeting of FBXW7 is confirmed by the software.…”
Section: Discussionmentioning
confidence: 99%
“…Notch1 signaling alteration is strongly related to T-ALL progression. 5,24 Since malfunction of FBXW7 has been reported in several types of human cancer, this protein seems as an appropriate choice for miRNA targeting studies. Therefore, the focus of the present study was to compare the expression levels of miR-32, miR-107, and FBXW7 using RT-qPCR in the plasma of patients with T-ALL.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Wendel et al have shown that miR-19 from the miR-17 ~ 92 cluster is sufficient to promote leukemogenesis in Notch1-induced T-ALL [139]. Regarding lncRNAs, Wallaerts et al performed an expression profile in primary T-ALL cases, which was able to classify T-ALL subgroups based on their expression pattern [140]. Trimarchi et al have reported that LUNAR1 (leukemia-induced noncoding activator RNA1) was a NOTCH1 target that plays an oncogenic role by regulating IGF1R expression [141].…”
Section: Transcriptional Targets Of Tal1 In T-all Cells: Non-coding Rnasmentioning
confidence: 99%